Realization of the Ideas of Labour Training of the Pupils of Ukrainian Schools at the Beginning of the XXth Century - Inna Yashchuk (Pedagogical Discourse, 2014)
The tasks of educational policy in Ukraine at the beginning of the XXth century, the principles of the system of people’s education, the ideas of development of «new school» have been marked in the article. It is mentioned that the structure of education was directed to labor, labor activity of schoolchildren and their teachers. That is why school cooperative societies were formed. Their aim was cooperative education through organization of different forms of labor activity on the basis of self-government and amateurishness. In the article, by the example of school cooperative of Proskuriv region, the characteristic and peculiarities of its activity have been revealed in details, the most widespread kinds of activity of pedagogues and schoolchildren have been described. The structure of teaching was concentrated on the labor, labor activity. In the offered material the «Code of laws of people’s education in the USSR» has been characterized, in which great significance was paid to the labor. Labor study was determined as teaching conscious attitude to all labor processes, respect to productive labor, development of volitional activity, abilities and individual peculiarities of pupils, their conscious attitude to the labor realization, correct physical education.